2022
DOI: 10.1002/alr.23053
|View full text |Cite
|
Sign up to set email alerts
|

Association of computed tomography scores to psychophysical measures of olfaction: A systematic review and meta‐analysis

Abstract: Background: While various sinus computed tomography (CT) scoring systems have been proposed and used in the literature, no single system has been identified as superior. The strength of associations between CT scoring systems and measures of olfaction also remains unclear.Methods: A systematic review of PubMed, CINAHL, Scopus, and the Cochrane Library was conducted following the Preferred Reporting Items for Systematic Reviews and Meta-Analyses guidelines. Studies that reported both CT scores and measures of o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 56 publications
0
1
0
Order By: Relevance
“…Several evaluation methods have been developed to evaluate the severity of olfactory cleft mucosal lesions in patients with CRS, including olfactory cleft CT scores and OCES 35,41,42 . Our study demonstrated that OCES and olfactory cleft CT scores among patients with CRS with olfactory dysfunction were significantly higher than those with CRS without olfactory dysfunction.…”
Section: Discussionmentioning
confidence: 64%
“…Several evaluation methods have been developed to evaluate the severity of olfactory cleft mucosal lesions in patients with CRS, including olfactory cleft CT scores and OCES 35,41,42 . Our study demonstrated that OCES and olfactory cleft CT scores among patients with CRS with olfactory dysfunction were significantly higher than those with CRS without olfactory dysfunction.…”
Section: Discussionmentioning
confidence: 64%